Qualidade e conservação sob refrigeração de frutos de noni (Morinda citrifolia L.) tratados com ácido giberélico e ethefhon na pré e póscolheita - Lima, Francisco Tadeu Dantas de (2016)
This study aimed to study the effects of application of plant growth regulators in the pre and post-harvest noni fruit and evaluate the postharvest quality when the fruits are subjected to low temperatures. The work was divided into three experiments. The first experiment evaluated the effects of pre application and GA3 post-harvest and ethephon on ripening and fruit quality of noni. Therefore, we obtained fruits of noni plants approximately three years, grown in Sector of Agriculture the Center Science Human, Social and Agricultural Federal University of Paraíba (CCHSA / UFPB). To evaluate the effect of regulators preharvest held spraying the plants noni 30 days before commercial fruit harvest with two doses of GA3 (100 and 200 mg.L-1 ) and two doses of ethephon (500 and 1000 mg.L-1 ) and control and to evaluate the effects of post-harvest fruits were harvested noni with fully whitish coloring shell (TE), these fruit were brought to the laboratory pair and divided into lots to be submitted to treatments with the application of plant growth regulators (GA3 100 and 200 mg.L -1 ; ethephon 500 and 1000 mg.L-1 ) and control, each treatment packed in polypropylene trays and stored at room temperature for 8 days. They were conducted evaluations using three replications of three fruits per treatment, at intervals of two days as the physical and physicochemical determinations. In the second experiment evaluated the effect of chilling injury in noni fruit postharvest quality subjected to low temperatures and identify less susceptible maturation stage. The fruits harvested noni were selected, sanitized and standardized for color and absence of injuries. This experiment was divided into two stages, the first stage: Fruits in yellowish green maturation stages (VA), yellow-white (AE) and fully off-white fruit (TE) were subjected to temperatures of 6, 9 and 12 °C for 5 days for determining the stage less susceptible to damage by the cold. In the second step: Fruits in TE stage were subjected to temperatures of 6, 7, 8, 9, 10, 11, 12 °C for 5 days. The evaluations in two steps were taken every 24 hours and for monitoring the evolution of chilling injury in fruits was performed subjective evaluations in the first stage and subjective, physical, physico-chemical and enzymatic activity in the second. The third experiment evaluated the effect of the application of plant growth regulators on quality and conservation of fruit noni under refrigeration. After the fruits of noni harvest they were divided into lots to be submitted to treatments with the application of plant growth regulators (GA3 200 mg.L-1 and ethephon 500 mg.L-1 ) and control, each treatment packed in polypropylene trays and stored at a temperature of 10 ± 0.5 °C / 75 ± 5% RH in growth chamber for 20 days. Evaluations were performed using three replications of three fruits per treatment, 4 day intervals as the physical and physic-chemical determinations. According to the results for the first experiment, it was found that ethephon pre-harvest application anticipated harvest in 20 days while applying 200 mg.L-1 GA3 delayed harvest in 15 days. The GA3 applied postharvest provided smaller mass loss values, soluble solids, titratable acidity and even greater firmness values and vitamin C from the fruits, while fruits treated with ethephon observed the reverse. For the second experiment, it was observed that the incidence of chilling vi injury was lower in fruits in AE stage to 12 °C and TE stage at temperatures 9 and 12 °C, with the emergence of damage by cooling only in the temperature 9 °C to 120 hours of exposure, while in the fruit VA and AE stage, maintained at temperatures of 6 and 9 °C, it was found that the severity of symptoms of damage by cold intensified over the time of exposure. In the third experiment, according to the results of the application of GA3 provided smaller mass loss values, soluble solids, titratable acidity and still higher stiffness values and vitamin C from the fruits, while in fruit treated with ethephon has been observed the inverse. It follows that the use of GA3 both pre- and post-harvest retards the maturation of noni fruit allowing to postpone the harvesting and extend the storage period matched against the ethephon anticipates maturation, becoming quickly fruit fit both for the crop and for immediate consumption and that noni fruit can be maintained at temperatures from 10 °C without showing signs of damage or loss by cold their normal metabolic processes.